Improved mechanical and tribological performance of bismaleimide composites with green synthesis of graphene/kapok-like ZnO. (July 2018) - Chen, Zhengyan; Li, Lin; Yao, Huanhuan; Guo, Liulong; Yan, Hongxia; Liu, Qi
Abstract: In this study, graphene/ZnO functionalized by active amine (NH2 -rGO/ZnO) was synthesized by a green solvothermal approach. To optimize the dispersibility of NH2 -rGO/ZnO, a series of experiments were performed by adjusting mass ratio of the precursors (NH2 -GO and Zn(NO3 )2 ·6H2 O). When it was 1: 1.5, ZnO nanosheets with kapok-like structure were attached to the surface of rGO. Then, different weight fractions of NH2 -rGO/kapok-like ZnO were doped into bismaleimide (BMI) resin to produce composites. The content of filler had an enormous influence on thermal, mechanical and tribological properties. The mechanical strengths of BMI composites firstly enhanced and then deteriorated by increasing the filler content. The 0.4 wt.% NH2 -rGO/ZnO/BMI system could attain the minimum values of coefficient of friction and volume wear rate. The improved friction and wear behavior of BMI composites was ascribed to the excellent interfacial adhesive strength between NH2 -rGO/ZnO and BMI matrix and outstanding self-lubricating effect of ZnO and rGO. Graphical abstract: Highlights: Graphene/kapok-like ZnO with active amine groups (NH2 -rGO/ZnO) was synthesized by a green solvothermal method. Bismaleimide (BMI) matrix composites with various weight fractions of NH2 -rGO/kapok-like ZnO were fabricated. The impacts of filler content on mechanical, tribological and thermal properties of BMI composites were investigated. 0.4 wt.% NH2 -rGO/ZnO/BMI composite exhibits the lowest values of friction coefficient and volume wear rate. BMI composite filled with 0.8 wt.% NH2 -rGO/ZnO showed the highest impact and flexural strengths in contrast to virgin BMI.